The Art of Debate in Islam: Textual Analysis and Translation of Ṭaşköprüzade’s Ādāb al-Baḥth wa al-Munāẓarah - Arif, Syamsuddin (Afkar: Jurnal Akidah dan Pemikiran Islam, 2020)
This article presents an analysis of a short treatise entitled Ādāb al-Baḥth wa al-Munāẓarah (The art of discussion and disputation) by the celebrated Ottoman scholar Abu al-Khayr ‘Iṣām al-Dīn Aḥmad ibn Muṣṭafā ibn Khalīl Ṭāshkubrīzādah or Ṭaşköprüzade (d. 968 AH/ 1561 CE). An overview of the nomenclature and a brief introduction about the author and his work will be presented along with an annotated English translation of the text in order to highlight Ṭaşköprüzade’s contribution to this nearly forgotten discipline.